2021
DOI: 10.3390/ijms22041570
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis and Conduction Abnormalities as Basis for Overlap of Brugada Syndrome and Early Repolarization Syndrome

Abstract: Brugada syndrome and early repolarization syndrome are both classified as J-wave syndromes, with a similar mechanism of arrhythmogenesis and with the same basis for genesis of the characteristic electrocardiographic features. The Brugada syndrome is now considered a conduction disorder based on subtle structural abnormalities in the right ventricular outflow tract. Recent evidence suggests structural substrate in patients with the early repolarization syndrome as well. We propose a unifying mechanism based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…In addition, RT is the summation of local activation time and local duration of repolarization, and in our ex vivo and in silico experiments, we studied heterogeneity in repolarization duration. RT heterogeneity may also result from heterogeneity in activation, for example, due to zigzag conduction through small conducting channels within the permanently inexcitable scar ( 24 ), sodium channel abnormalities ( 25 ), or post-repolarization refractoriness ( 26 ). Considering these various sources of “excitability heterogeneity” would allow us to extend our reasoning to other myocardial substrates or even arrhythmias of other electromechanical organs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RT is the summation of local activation time and local duration of repolarization, and in our ex vivo and in silico experiments, we studied heterogeneity in repolarization duration. RT heterogeneity may also result from heterogeneity in activation, for example, due to zigzag conduction through small conducting channels within the permanently inexcitable scar ( 24 ), sodium channel abnormalities ( 25 ), or post-repolarization refractoriness ( 26 ). Considering these various sources of “excitability heterogeneity” would allow us to extend our reasoning to other myocardial substrates or even arrhythmias of other electromechanical organs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several excellent studies regarding the overlap between BrS and other cardiac pathologies, including early repolarization syndrome (5), arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) (6-9), progressive cardiac conduction defect (Lenègre syndrome) (10,11), LQTS (12)(13)(14), Wolff-Parkinson-White (15,16), hypertrophic cardiomyopathy (17,18), atrial flutter (19), and atrial fibrillation (20)(21)(22)(23). Therefore, whatever mechanisms that ultimately lead to the development of the BrS ECG pattern may also be involved in other pathways that result in other cardiac pathologies.…”
Section: Brugada Syndrome and Cardiac Disorders Overlapmentioning
confidence: 99%
“…The typical symptoms of BrS are syncope and cardiac arrest due to ventricular fibrillation (VF) or ventricular tachycardia (VT), in the absence of overt cardiac structural changes, typically between 30 and 50 years of age (3,4). BrS has been associated with several other cardiac disorders, such as early repolarization syndrome (5), arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) (6)(7)(8)(9), progressive cardiac conduction defect (Lenègre syndrome) (10,11), LQTS (12)(13)(14), Wolff-Parkinson-White (15,16), hypertrophic cardiomyopathy (17,18), atrial flutter (19), and atrial fibrillation (20)(21)(22)(23). In addition, BrS has also been associated with non-cardiac pathologies, such as epilepsy, thyroid disorders, cancer, skeletal muscle sodium channelopathies, laminopathies, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Nademanee et al showed an increased collagen content in the right ventricular outflow tract (RVOT) that shows epicardial surface and intramyocardial fibrosis, in addition to diminished gap junction protein expression. This fibrosis was associated with conduction delay in the RVOT [ 33 , 34 ]. Our results go in the same direction as these articles and seem to indicate that despite being an arrhythmogenic disease there are certain structural abnormalities in this syndrome.…”
Section: Discussionmentioning
confidence: 99%